COVID-19, home advantage in professional soccer,and betting market efficiency - Fischer, K.; Haucap, J. (Universität Düsseldorf, Institute for Competition Economics, 2021)
Fan support has often been considered to be a main driver of the home advantage in sports. Using the natural experiment of ghost games during the COVID-19 pandemic in German professional soccer, we test this claim. Indeed, we identify a reduction in the home performance - though with much heterogeneity across leagues. We moreover observe the home advantage to recover over time. In analysing whether betting markets anticipated this drop in the home advantage and its recovery, we test the efficient market hypothesis. We find that betting odds do not properly reflectthe effect of ghost games regarding changes in the home advantage. Furthermore, we present evidence for a slow to non-existent adaptation process with respect to new match results, indicating a lack of semi-strong efficiency. Basedon these findings, we show how simple betting strategies could have exploited the discussed phenomenon.